Vitamin D binding protein variants associate with asthma susceptibility in the Chinese han population - Zhang Youming; Willis-Owen Saffron A; Jiang Lei; Li Fei; Gao Jinming (BMC, 2011)
Abstract Background Asthma is a genetically heterogeneous disease. Polymorphisms of genes encoding components of the vitamin D pathway have been reported to associate with the risk of asthma. We have previously demonstrated that vitamin D status was associated with lung function in Chinese asthma patients. In this study, we tested whether polymorphisms of genes encoding for vitamin D receptor (VDR), vitamin D 25-hydroxylase (CYP2R1) and vitamin D binding protein (GC) were associated with asthma in the Chinese Han population. Methods We sequenced all 8 exons of VDR and all 5 exons of CYP2R1 in a Chinese case-control cohort of asthma consisting of 467 cases and 288 unrelated healthy controls. Two mutations were identified in these regions. These variants were specified as rs2228570 in exon 2 of VDR and rs12794714 in exon 1 of CYP2R1. We also genotyped two common polymorphisms in GC gene (rs4588 and rs7041) by a PCR-restriction fragment length polymorphism (RFLP) method. We analyzed the association between these 4 polymorphisms and asthma susceptibility and asthma-related traits. Results Polymorphic markers in VDR and CYP2R1 were not associated with asthma in the Chinese Han cohort. Importantly, variants in GC gene, which give rise to the two most common electrophoretic isoforms of the vitamin D binding protein, were associated with asthma susceptibility. Compared with isoform Gc1, Gc2 was significantly associated with the risk of asthma (OR = 1.35, 95% CI = 1.01-1.78 p = 0.006). Conclusions The results provide supporting evidence for association between GC variants and asthma susceptibility in the Chinese Han population.